Genotoxic and Cytotoxic Effects of Favimol in White Mice - Alyaa Fadhil Abbas; Dr. Wajdi Sabeeh Sadeq (Migration Letters, 2023)
The current study aimed to assess the genotoxicity and cytotoxicity of favimol in Swiss albino mice (Mus musculus). The genotoxic and cytotoxic effects were examined at doses of 1200, 2400, and 3200 mg/kg. The evaluation was based on cytogenetic indicators such as chromosomal abnormalities in primary spermatocytes and morphological abnormalities in sperm. The results demonstrated a significant increase in mean differences for numerical chromosomal abnormalities during Diakinesis of the first metaphase in the treated groups. The highest value was observed at the 3200 mg/kg dose, with a value of 7.840 ± 0.52. Similarly, the mean values of structural chromosomal abnormalities reached their peak at the dose of 3200 mg/kg, with a value of 17.80 ± 0.54. The study also revealed the occurrence of morphological abnormalities in the sperm head after exposure to the drug. This led to a significant increase in mean differences for head abnormalities in the treated groups, with the highest value recorded at the 2400 mg/kg dose (256.60 ± 3.10). It is noteworthy that all animals administered the 3200 mg/kg dose died within 5 days, and this outcome was consistent across three repetitions of the experiment.